EFFECT OF INFUSION OF A COMBINATION OF TEMU IRENG, TEMULAWAK, KENCUR, GINGER ON ERYTHROCYTE COUNT AND HEMATOCRIT LEVELS IN ANEMIA WHITE RATS - Miranti, Indira Pipit; Khumaeni, Eko Hidayaturrohman; Maghfira, Windy Risa; Gunawan, Gunawan; Kusuma, Jaka Wijaya (International Journal of Multidisciplinary Research and Literature, 2025)
Anemia is a condition in which the body experiences a decrease in hemoglobin levels, erythrocyte count, and hematocrit levels. The rhizomes of temu black, temulawak, kencur and ginger, contain compounds that have antioxidant and anti-inflammatory activities that can prevent and repair damage from oxidative stress in the body that causes anemia. This study aims to determine the effect and optimal frequency of infusion administration of a combination of temu ireng, temulawak, kencur, and ginger on erythrocyte count and hematocrit levels in white rats of the wistar strain anemia. The method used is experimental research with a pre-post-test control design. The four rhizomes used in this study contribute to the treatment of anemia. The isoflavone content in black temu and curcumin in curcumin in curcumin can prevent damage to erythrocytes due to oxidative stress of sodium nitrite exposure. Other ingredients such as Ethyl p-methoxycinnamate in ginger act as an anti-inflammatory by reducing the production of cytokines IL-1 and TNF-ɑ. Then the content of 6-gingerol in ginger can stop the formation of hepcidin which inhibits the absorption of iron, so that the process of forming red blood cells can continue in the bone marrow. It can be concluded that the combination of infusion of temu black, temulawak, kencur and ginger can increase the number of erythrocytes and hematocrit levels in anemia white rats. Meanwhile, the optimal frequency in increasing the number of erythrocytes and hematocrit levels occurred in the P2 group with a frequency of administration 2 times a day.